Optomechanical measurement of the stiffness of single adherent cells1. Issue 17 (7th September 2015) - Park, Kidong; Mehrnezhad, Ali; Corbin, Elise A.; Bashir, Rashid
<x xml:space="preserve">Abstract</x> We demonstrate a novel optomechanical technique to characterize the stiffness of single adherent cells on a substrate in a non-invasive manner.